Late Holocene hydrologic variability and ecosystem structure from rock hyrax middens in Dhofar, Oman - Horisk, Kaitlyn E.; Ivory, Sarah J.; Freeman, Katherine H.; Baczynski, Allison A.; McCorriston, Joy; Anderson, Andrew; Anderson, R. Scott; Al-Kathiri, Ali (Frontiers in Earth Science, 2024)
Over 1/3 of the Earth’s human population relies on dryland ecosystems for food and water resources. While these ecosystems are highly sensitive to changes in climate, we lack observational data as to how changes in hydrology influences plant communities. Paleoecological data for southern Arabia show woodland communities transitioned to more dry-adapted herbaceous plants, which suggests rainfall decreased across the Holocene. To assess relationships between hydrology and ecology, we employed leaf wax n-alkane distributions, δ13Cwax, and δDwax records from rock hyrax (Procavia capensis) middens in Dhofar, Oman. The biomarker properties allowed reconstruction of changes in C3/C4 vegetation and local moisture availability, in tandem with community changes represented by a published pollen record. To constrain interpretations, n-alkane analyses were conducted on herbarium specimens of leaves collected in Dhofar. For the modern specimens, xeric plants typically contained longer homologues than mesic plants. Across the fossil middens (4,038–109 cal yrs BP), the proportions of plant-wax homologues do not show major changes, and thus do not suggest a shift between xeric versus mesic plants. Similarly, δ13Cwax values indicate little or no change in the distributions of C3 and C4 vegetation. Limited δDwax data from the middens confirm overall drying occurred into the late Holocene, punctuated by a wetter pulse at ∼1.6 ka. Taken together, plant wax distributions and isotope data indicate changes in moisture availability across the late Holocene did not alter the structural composition of the plant communities and that the proportion of C3/C4 vegetation remained stable. We infer vegetation changes associated with late Holocene drying involved reshuffling of community composition and not major changes in vegetation structure. Additionally, this study demonstrates that leaf wax n-alkanes from rock hyrax middens provide a method to reconstruct changes in climate and vegetation in dryland ecosystems where other archives are scarce.